Hybrid renewable energy photovoltaic and darrieus VAWT as propulsion fuel of prototype catamaran ship - Budhy Setiawan; Ekananda Sulistyo Putra; Indrazno Siradjuddin (Bulletin of Electrical Engineering and Informatics, 2021)
Currently, marine transportation in the world still uses fossil fuels. In addition to running low on supplies, fossil fuels also cause emissions that cause global warming. Sea transportation generates around 1,000 million tonnes of CO2 emissions. Therefore, the exploration of alternative energy is becoming a popular research direction. Several renewable energy sources include solar and wind energy. Indonesia has an average wind speed of above 8 m/s at sea. Also, the energy potential of the sun is around 4.8 kWh/m2. Based on the potential of these renewable energy sources, this study discusses the potential of renewable energy sources from sunlight and wind, which are implemented in the prototype catamaran ship. The results obtained from the experiment, the total energy of photovoltaic (PV) and wind turbine generators is 774 Wh. This energy can be used to charge a battery with a battery specification of 35Ah for 6 hours.